A non-enzymatic thermally reduced Cu nanoparticle based graphene-resorcinol benzaldehyde glucose sensor. (February 2015) - Khalid, B.; Meng, Q. H.; Cao, B.
Abstract : A non-enzymatic graphene based resorcinol–benzaldehyde glucose sensor decorated with copper nanoparticles (Cu NPs) was developed by a fast thermal reduction method. Cu NPs were synthesised by stirring various concentrations of [Cu(NH3 )2 ] with graphene based resorcinol–benzaldehyde sheets. Subsequently physically adsorbed Cu 2+ were thermally reduced under Ar gas. The electrochemical behaviour of Cu NPs based electrodes was investigated by cyclic voltammetry, which shows a very high oxidation of glucose in a neutral solution. All electrodes can be applied for the quantification of glucose with a linear range of 0·30–30·0 μM. The Cu NPs displayed a synergistic effect towards the oxidation of glucose with high stability and selectivity, showing higher oxidation current and negative shift in peak potential. Characterisations were done by X-ray diffraction, thermogravimetric analysis and transmission electron microscopy. Besides, synthesis method is very simple, convenient, and fast, which is promising for the development of non-enzymatic glucose sensors.